RADIO-TECHNICAL FLIGHT SUPPORT MILITARY AND CIVIL AVIATION – THE STRATEGIC PROBLEM OF RUSSIA ARCTIC ZONE - N. I. Didenko; B. P. Eliseev; O. I. Sauta; A. Yu. Shatrakov; A. V. Yushkov (Научный вестник МГТУ ГА, 2017)
It should be noted that a number of countries consider that the Arctic is the property of all mankind and therefore the legal regime of the usage of this region territory is necessary to be reconsidered. The intensification of the armed forces activities on the northern borders is caused by aggravated international disagreements on the issues of territorial influence in this region, by the need to ensure the safety of increasing freight traffic through the Northern Sea Route and also by an increase in production capacities of domestic extractive enterprises on the shelf. The article deals with the challenge of the accelerated development in the Arctic region of Russia. It is noted that the major role in the solution of this problem belongs to an air-transport complex which is almost the only means to provide the operational availability to objects in the region. For the effective usage of the air-transport complex the approach based on the concept of radio-technical flight support, founded on the technologies of global navigation satellite systems and automatic dependent observation is offered. The existence of readymade technical solutions for these technologies implementation allows to accelerate the solvation of social and economic development problems of the Arctic region in general, alongside with the problems of national security of Russia.